Neurosarcoidosis Associated with Psychiatric Symptoms: Case Report - Neves, Maick Wilen Fernandes; Aguiar, Paulo Henrique Pires de; Belsuzarri, Telmo Augusto Barba; Zeviani, Wolnei Marques; Mattos, João Flavio de Araújo; Navarro, Juliano Nery; Marques, Renata de Melo Braga; Francisco, Letícia Marissol de Souza (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Background Sarcoidosis is a granulomatous disease predominant in women and black men that has inflammatory origin of unknown etiology; neurosarcoidosis is a rare and critical presentation of the disease.Case description A 26-year-old black female presented frontal headache for 1 year, as well as behavioral and mood changes for 15 days. Skull tomography and nuclear magnetic imaging of the skull revealed damaged meninges, a right frontal bone lesion, and an intraparenchymal contrast-enhancing lesion. Screening with computed tomography (CT) scans was performed, and it showed signs of bronchiectasis in the lower third of the right lung, but it was asymptomatic. The biopsy showed signs of reactional lesion with the presence of non-caseating granulomas. After the treatment with corticosteroids, the patient presented progressive improvement.Conclusions Neurosarcoidosis is a rare and critical pathology of sarcoidosis that presents a lytic bone lesion and clinical psychiatric symptoms; neurosarcoidosis is also rare in the literature.
Keywords: sarcoidosis; neurosarcoidosis; psychiatric manifestations; pathology